A new receptor of aromatic Carboxylates based on a trismacrocyclic complex of Copper(II) and operating according to the molecular recognition principle - Comba, Peter (Theoretical and experimental chemistry, 2001)
The reaction of mono-, bis-, and trismacrocyclic complexes of copper(II) with aromatic carboxylates was studied by a spectrophotometric method. It was shown that the largest spectral changes are observed during the reaction of the trinuclear complex with its complementary benzene-1,3,5-tricarboxylate anion. The receptor also differentiates regioselectively between the isomers of phthalic acids. The crystal structure of the 1 : 2 adduct of the trismacrocyclic complex of copper with benzenetricarboxylate was determined.